Designing Culturally Responsive Organized After-School Activities. (January 2017) - Simpkins, Sandra D.; Riggs, Nathaniel R.; Ngo, Bic; Vest Ettekal, Andrea; Okamoto, Dina
Organized after-school activities promote positive youth development across a range of outcomes. To be most effective, organized activities need to meet high-quality standards. The eight features of quality developed by the National Research Council's Committee on Community-Level Programs for Youth have helped guide the field in this regard. However, these standards have largely been defined in terms of universal developmental needs, and do not adequately speak to the growing ethnic and racial diversity within the United States, which is further complicated by issues of power and social class differences. Given U.S. population shifts and after-school funding priorities, the time has come to consider new ways to provide organized after-school activities that are responsive to youth's culture and everyday lives. The goal of this article is to explore how we can help ensure that after-school activities are culturally responsive and address the specific needs of the youth who participate in these activities. Based on theory and empirical evidence, we provide proposed practices of cultural responsiveness for each of the eight features of quality for program structure and staff. The article concludes with future directions for research and strategies to implement culturally responsive practices and harness resources.